ANALISIS PERATAAN LABA, PROFITABILITAS DAN NILAI PERUSAHAAN PADA PT KALBE FARMA TBK - Fera Maulina (STIE 'INDONESIA' Pontianak, 2020)
Financial report describe the financial condition and results of operations of a company at a certain time or period of time. The writer analyzes PT Kalbe Farma's financial report by looking at Income Smoothing, Profit Margin Ratio, Return On Assets, Return On Equity, Basic Earning Power, Dividend Yield, Dividend Payout Ratio, Price Earning Ratio, and Market to Book Value Ratio. In this study, the writer uses quantitative analysis data with descriptive method. The data used is secondary data that is obtained from the financial report of PT Kalbe Farma Tbk, documentation studies, and literature studies in data collection techniques. The results of this study show that the Eckel Index at PT Kalbe Farma Tbk is 0.9481, which means that PT Kalbe Farma Tbk Company belongs to the category of companies that practice income smoothing. Profitability at PT Kalbe Farma Tbk shows that the performance of the company PT Kalbe Farma Tbk is not good because it has decreased in 2013-2015. In 2016, the company began to increase company performance which can be seen from the increase in the value of profitability. The value of the Company at PT Kalbe Farma Tbk is good even though overall it experiences fluctuations every year.